2003
DOI: 10.1021/jp035714l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound on Ester Hydrolysis in Binary Solvents

Abstract: We have investigated the kinetics of the acid-catalyzed hydrolysis of ethyl, propyl, and butyl acetates in aqueous binary mixtures of ethanol and of 1,4-dioxane without sonication and under ultrasound at 22 kHz. Various rate enhancements were found in the region from pure water up to 50 wt % ethanol and 60 wt % dioxane. The calorimetric measurements performed in the same region indicated an insignificant effect of the solvent composition on the ultrasonic power. It was concluded that the sonochemical accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 49 publications
(95 reference statements)
2
34
0
Order By: Relevance
“…Values in parentheses represent the relative abundance. tion bubble, where transient hot spots with locally extremely harsh conditions occur, are generally accepted as the origin of the chemical effects [35,36]. Another beneficial effect of ultrasonication compared to the corresponding silent reaction is the efficient removal of bubbles from the bulk solution.…”
Section: Selection Of the Reaction Conditionsmentioning
confidence: 99%
“…Values in parentheses represent the relative abundance. tion bubble, where transient hot spots with locally extremely harsh conditions occur, are generally accepted as the origin of the chemical effects [35,36]. Another beneficial effect of ultrasonication compared to the corresponding silent reaction is the efficient removal of bubbles from the bulk solution.…”
Section: Selection Of the Reaction Conditionsmentioning
confidence: 99%
“…For the acid-catalyzed hydrolysis of ethyl acetate we observed a similar dependence of the sonication effect on solvent composition. [19,20] These results initially led us to think that sonication effects were merely related to a perturbation of the solvent system. However, on replacing ethyl acetate with more hydrophobic esters, we observed a dramatic change in the dependence of the sonication effect on solvent composition, which obliged us to revise our early point of view.…”
Section: Resultsmentioning
confidence: 99%
“…Solute-solvent interactions in these complicated systems proved to be particularly important in clarifying the matter. [20,23] Recent spectroscopic, X-ray diffraction, and mass spectrometric investigations have shed light on the structure of ethanol-water solutions. [30][31][32] It has been concluded that small additions of ethanol in the range of 0 < X E < 0.08 (X E being the ethanol molar ratio) exert a strong structure-making effect accompanied by an increase in the self-association of water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations